3 kW narrow linewidth high spectral density continuous wave fiber laser based on fiber Bragg grating. (January 2021) - Huang, Yusheng; Xiao, Qirong; Li, Dan; Xin, Jingtao; Wang, Zehui; Tian, Jiading; Wu, Yulun; Gong, Mali; Zhu, Lianqing; Yan, Ping
Highlights: The highest power spectral density reported by an all-fiber FBG-based fiber laser. Using Long-grating-length FBG to acquire a high PSD seed laser. Multiple methods were taken in the amplifier to suppress spectrum broadening. Abstract: We demonstrated a narrow linewidth monolithic fiber-Bragg-grating-based (FBG-based) MOPA configuration fiber laser with a high power spectral density (PSD). In the oscillator, long-grating-length FBG with narrow reflection bandwidth was employed, combined with a short length resonant cavity, contributing to a narrow linewidth high PSD seed laser. In the amplifier stage, methods were taken to suppress spectrum broadening, such as large-core active fiber and wavelength-stabilized laser diode. As a result, the fiber laser achieved an output power of 3010 W, a spectral 3-dB bandwidth of 103 pm, and a PSD of 29.3 pm/kW. To the best of our knowledge, this is the highest PSD reported by an all-fiber FBG-based fiber laser.